The study of the interaction of 5-(2-hydroxyphenyl)-1,2,4-polytriazolylacetic acid esters with uranyl ions - Vashchenko, O.V.; Khomenko, D.M.; Doroschuk, R.O.; Raspertova, I.V.; Lampeka, R.D. (Reports of the National Academy of Sciences of Ukraine, 2017)
For the first time, three new ligands — derivatives of 5-(2-hydroxyphenyl)-1,2,4-polytriazolylacetic acids — and the coordination compounds of uranyl ions on their basis have been synthesized. The obtained compounds are studied by means of IR and NMR spectroscopies. It is established that ethyl esters H3L1 and H4L2 interacting with uranyl ions form complexes of the corresponding carboxylic acids. The ester group of ligand H5L3 does not hydrolyze under the same condition, and the ester group does not form coordination bonds with an uranyl ion.